VD_FINDINFO HC / 2011 / 607 vom 27. September 2011 - VD Tribunal cantonal (2011)
DONATION, FORME ÉCRITE, PROMESSE DE PAYER, INDEMNITÉ DE DÉPART | 1 CO, 16 CO, 18 CO, 239 CO, 451 ch. 2 CPC, 452 al. 2 CPC, 46 LJT, 405 al. 1 CPC (CH)